2017
DOI: 10.1245/s10434-017-6078-x
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the 8th Edition of the AJCC TNM Staging System for Gastric Cancer using the National Cancer Database

Abstract: The 8th edition is valid for U.S. populations, showing clear separation of data with preservation of group order.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
204
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 276 publications
(229 citation statements)
references
References 20 publications
4
204
0
Order By: Relevance
“…All patients underwent an adjuvant chemotherapy regimen with S-1 at our institute. Tumor stages were assessed according to the Union for International Cancer Control classification 35 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All patients underwent an adjuvant chemotherapy regimen with S-1 at our institute. Tumor stages were assessed according to the Union for International Cancer Control classification 35 .…”
Section: Methodsmentioning
confidence: 99%
“…All patients underwent an adjuvant chemotherapy regimen with S-1 at our institute. Tumor stages were assessed according to the Union for International Cancer Control classification 35 .Peripheral blood (7 ml) was obtained from each patient before surgery. The blood was transferred into sodium heparin tubes (BD Vacutainer, Franklin Lakes, NJ) and immediately subjected to a three-spin protocol (1500 r.p.m.…”
mentioning
confidence: 99%
“…Although the TNM 8th edition proved to be superior to the TNM 7th edition in predicting overall survival, [4][5][6][7] both editions are subject to the risk of stage migration. The phenomenon of stage migration occurs when the number of examined lymph nodes is insufficient.…”
Section: Introductionmentioning
confidence: 98%
“…For this reason, the prognostic accuracy of the node subsection (N) of the American Joint Committee on Cancer (AJCC) tumor‐node‐metastasis (TNM) classification has been pursued in all its late editions. Although the TNM 8th edition proved to be superior to the TNM 7th edition in predicting overall survival, both editions are subject to the risk of stage migration. The phenomenon of stage migration occurs when the number of examined lymph nodes is insufficient.…”
Section: Introductionmentioning
confidence: 99%
“…The 8th edition (8th) of the AJCC staging system was released in October 2016 and was recommended as a replacement for the older version in 2018 [1]. Research on the prognostic performance of the latest version has been gradually reported [2][3][4][5][6]. In our opinion, the 8th AJCC-TNM staging system can better distinguish the prognosis of GC patients.…”
Section: Introductionmentioning
confidence: 99%